Peripheral neuropathy and benign IgG paraproteinaemia. - Read, D J (1978)
Three patients with peripheral neuropathy and an associated benign IgG paraproteinaemia are described. No direct immunological evidence for an aetiological role of the paraprotein was found, and the implications of this are discussed.